Standar Arsitektur Pasar Tradisional Pasca Pandemi - Hardiana, Ana; Purwani, Ofita; Febriyani, Atika (ARSITEKTURA, 2021)
There have been architectural standards for many types of buildings such as the ones for hospitals, hotels, and shopping malls. Those standards were developed with an assumption that we live free from contagious diseases like Covid-19. The world situation in the last decade has shown that new contagious diseases are on the rise, bringing people’s lives at risk. It is then very urgent to review the existing architectural standards to fit our new needs. This paper then focuses on a review on architectural standard, which in this case is traditional market to propose a new standard. To do that we review the existing standard and the existing literature on Covid-19, before developing a proposal for a new standard for traditional market in Indonesia. The proposal shows a revision in the layout, room size, internal and external circulation, the use of materials, lighting, and ventilation.